Overcoming a stumbling block: Challenges of English-medium instruction for Vietnamese tertiary Students - Duong Minh Tuan; Le Thi Diem Lan (Studies in English Language and Education)
English as a medium of instruction (EMI) is a growing global phenomenon, and non-native English-speaking (NNES) countries have increasingly adopted EMI courses in higher education over the past few decades in response to the momentum of globalization and internationalization. However, implementing EMI initiatives in Vietnam has faced numerous challenges and constraints. While there has been extensive research on the difficulties faced by content teachers in EMI classrooms, there is a lack of scholarly inquiry into the challenges students encounter in EMI programs in Vietnam. Therefore, this study aimed to explore the challenges faced by university students in EMI classrooms. The study used a mixed-methods research approach, gathering quantitative and qualitative data through a questionnaire and semi-structured interviews, respectively. The participants were 120 students enrolled in EMI programs at a public university in the Mekong Delta of Vietnam. The results revealed that students faced significant challenges in their EMI learning course. Precisely, they needed help comprehending course materials, understanding lectures, taking examinations, and participating in classroom discussions. Based on the results of the study, practical implications were discussed to enhance the effectiveness of EMI programs in higher education contexts.